115 Neurosurgical Resident Attrition. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - White, Michael D; Agarwal, Nitin; Pannullo, Susan C; Chambless, Lola B
Abstract: INTRODUCTION: Resident attrition creates a profound burden on trainees and residency programs. This study aims to analyze trends in resident attrition within Neurosurgery . METHODS: This study followed a cohort of 1275 residents who started neurosurgery residency from 2005 to 2010. A list of residents matching during this time was obtained from the American Association of Neurological Surgeons. Residents who did not finish their residency training at the program in which they started were placed into 1 of 5 groups: transferred neurosurgery programs; transferred to a different specialty; left clinical medicine; deceased; or unknown. A thorough internet search was conducted for residents who did not complete their training at their first neurosurgery program. Variables leading to attrition were also analyzed, including age, gender, presence of advanced degree (PhD), postgraduate year (PGY), and geographical region of program. RESULTS: Residents starting neurosurgery residency from 2005 to 2010 had an overall attrition rate of 11.15%. There was no statistically significant difference in attrition rates between the years ( P = .337). The outcomes for residents in the attrition group were found to be: 33.61% transferred neurosurgery programs, 56.30% transferred to a different medical specialty, 8.40% left clinical medicine, and 1.68% were deceased. It was observed that women had a higher attrition rate (18.50%) than men (10.35%) ( P < .01). Most attrition (65.07%) occurred during the PGY 1 or 2 yr. The attrition group was also observed to be significantly older at the beginning of residency training, with a mean of 31.69 yr of age compared to 29.31 in the nonattrition group ( P < .001). No significant difference was observed in the attrition rates for residents with a PhD (9.86%) compared to those without a PhD ( P = .472). CONCLUSION: Resident attrition remains a significant problem within neurosurgical training, and future studies should focus on targeted interventions to identify at risk individuals to help them succeed in their medical careers.